2023
DOI: 10.1111/jgs.18304
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contributions of modifiable risk factors to serious falls and fragility fractures among older persons living with HIV

Abstract: Background Although 50 years represents middle age among uninfected individuals, studies have shown that persons living with HIV (PWH) begin to demonstrate elevated risk for serious falls and fragility fractures in the sixth decade; the proportions of these outcomes attributable to modifiable factors are unknown. Methods We analyzed 21,041 older PWH on antiretroviral therapy (ART) from the Veterans Aging Cohort Study from 01/01/2010 through 09/30/2015. Serious falls were identified by Ecodes and a machine‐lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…However, less is known about the relationship between polypharmacy and adverse outcomes in PWH and whether there are sex differences in polypharmacy in PWH after accounting for potential differences in comorbidities [ 18–21 ]. Prior studies of polypharmacy in PWH found associations between polypharmacy and adverse outcomes, including serious falls [ 22 ] and impaired cognition [ 19 ]. However, a key factor that limits our understanding of the relationship between polypharmacy and adverse outcomes in PWH with virologic suppression is the paucity of studies that have focused on large cohorts of mixed-sex, aging PWH on ART, with a detailed inventory of medication use alongside detailed accounting of comorbidities and other important confounding factors.…”
mentioning
confidence: 99%
“…However, less is known about the relationship between polypharmacy and adverse outcomes in PWH and whether there are sex differences in polypharmacy in PWH after accounting for potential differences in comorbidities [ 18–21 ]. Prior studies of polypharmacy in PWH found associations between polypharmacy and adverse outcomes, including serious falls [ 22 ] and impaired cognition [ 19 ]. However, a key factor that limits our understanding of the relationship between polypharmacy and adverse outcomes in PWH with virologic suppression is the paucity of studies that have focused on large cohorts of mixed-sex, aging PWH on ART, with a detailed inventory of medication use alongside detailed accounting of comorbidities and other important confounding factors.…”
mentioning
confidence: 99%